THE COMPARISON OF BRICK SHRINKAGE VALUE ON THE ADDITION OF COCONUT AND RICE HUSK ASH - Masthura Masthura; Anggun Hermi Palupi; Abdul Halim Daulay (Universitas Islam Negeri Sumatera Utara Medan, 2019)
A research has been conducted on the comparison of the value of burnt shrinkage and porosity of bricks by adding a mixture of coconut husk ash and rice husk ash. The purpose of this study is to determine the effect of variations in the addition of coconut husk ash and rice husk to the value of burnt shrinkage and porosity of bricks. Porosity testing was carried out due to the addition of a mixture of coir ash and rice husk to produce porous bricks. Variations in the percentage of clay with a mixture (coconut husk ash and rice husk ash) include 100%:0%, 95%:5%, 90%:10%, 85%:15% and 80%:20%. The results obtained for the value of burnt shrinkage from the addition of rice husk ash in brick making results are smaller than the addition of coconut coir ash. The results of the shrinkage value of the addition of coconut coir ash and rice husk already meet the SNI 15-2094-2000 standards that is <15%. However, the porosity value from the addition of coconut husk ash and rice husk ash does not meet the standards required in SNI 15-2094-2000 because> 20%. With large porosity values exceeding SNI 15-2094-2000 standards, the suggested bricks are used as an inner wall and cannot be used as a face wall. Keywords: burnt shrinkage, coconut husk ash, porosity, and rice husk ash.